Optimization for the vehicle routing problem with the capacity constrained - Fatima Zohra Siad (My University, 2026)
This thesis addresses the Capacitated Vehicle Routing Problem, one of the most important combinatorial optimization problems in Operations Research. The problem consists of determining optimal routes for a fleet of vehicles departing from a single depot in order to serve a set of customers with known demands, while respecting vehicle capacity constraints and minimizing the total travel distance. Since this problem belongs to the class of NP-hard problems, exact methods become ineffcient when dealing with large-scale instances, which motivates the use of approximate approaches to obtain good-quality solutions within a reasonable computational time. In this work, we propose a hybrid approach combining Local Search and Simulated Annealing. This approach aims to improve solution quality by balancing exploration of the solution space and intensification in promising regions, while avoiding local optima. The proposed method is tested on a real-world case study, and the results show a significant improvement in total distance and solution quality compared to the current approach. -------------------------------------------------------- تتناول هذه المذكرة مشكلة توجيه المركبات ذات السعة المحدودة، وهي إحدى مسائل التحسين التوافقي في مجال بحوث العمليات. تتمثل هذه المشكلة في تحديد مجموعة من المسارات المثلى لأسطول من المركبات ينطلق من مستودع واحد بهدف خدمة مجموعة من الزبائن ذوي طلبات معروفة، مع احترام قيد سعة المركبات وتقليل المسافة الإجمالية المقطوعة. ونظرًا لكون هذه المشكلة تنتمي إلى الفئة الصعبة، فإن الطرق الدقيقة تصبح غير فعالة عند التعامل مع الحالات كبيرة الحجم، مما يستدعي استخدام أساليب تقريبية للحصول على حلول جيدة في وقت حسابي معقول. في هذا العمل، نقترح مقاربة هجينة تجمع بين البحث المحلي وخوارزمية التلدين المحاكى، بهدف تحسين جودة الحلول وتقليل المسافة الإجمالية المقطوعة. تم تطبيق الطريقة المقترحة على حالة دراسية، وأظهرت النتائج تحسنًا ملحوظًا في جودة الحلول مقارنة بالمنهجية الحالية. --------------------------------------------------------------- Ce mémoire traite du problème de tournées de véhicules à capacité limitée, l’un des prob lèmes les plus importants en optimisation combinatoire dans le domaine de la recherche opérationnelle. Ce problème consiste à déterminer des tournées optimales pour une flotte de véhicules partant d’un dépôt unique afin de servir un ensemble de clients ayant des demandes connues, tout en respectant la contrainte de capacité des véhicules et en minimisant la distance totale parcourue. Étant donné que ce problème appartient à la classe des problèmes NP-difficiles, les méthodes exactes deviennent inefficaces lorsqu’il s’agit de grandes instances, ce qui motive l’utilisation d’approches approximatives permettant d’obtenir de bonnes solutions dans un temps de calcul raisonnable. Dans ce travail, nous proposons une approche hybride combinant la recherche locale et le recuit simulé. Cette approche vise à améliorer la qualité des solutions en équilibrant l’exploration de l’espace de recherche et l’intensification dans les régions prometteuses, tout en évitant les optima locaux. La méthode proposée est testée sur une étude de cas, et les résultats obtenus montrent une amélioration notable de la distance totale et de la qualité des solutions par rapport à l’approche actuelle.
Keywords: Combinatorial optimization; Vehicle Routing Problem; Operations Research; Approximate methods; Local Search; Simulated Annealing; hybrid optimization.; التحسين التوافقي، مشكلة توجيه المركبات، بحوث العمليات، البحث المحلي، التلدين المحاكى، التحسين الهجين; Optimisation combinatoire; problème de tournées de véhicules; recherche opérationnelle; méthodes approximatives; recherche locale; recuit simulé; optimisation hybride.